2010 VOLCANIC ACTIVITY IN ALASKA, KAMCHATKA, AND THE KURILE ISLANDS: SUMMARY OF EVENTS AND RESPONSE OF THE ALASKA VOLCANO OBSERVATORY - Neal C.A.; Herrick J.A.; Girina O.A.; Chibisova M.V.; Rybin A.V.; Mcgimsey R.G.; Dixon J. (My University, 2014)
The Alaska Volcano Observatory (AVO) responded to eruptions, possible eruptions, volcanic unrest or suspected unrest at 12 volcanic centers in Alaska during 2010. The most notable volcanic activity consisted of intermittent ash emissions from long-active Cleveland volcano in the Aleutian Islands. AVO staff also participated in hazard communication regarding eruptions or unrest at seven volcanoes in Russia as part of an ongoing collaborative role in the Kamchatka and Sakhalin Volcanic Eruption Response Teams.
Keywords: 38.37.25 Вулканология; Карымский; Кизимен; Безымянный; Шивелуч; Ключевской